A qualitative study of Thai HIV-positive young men who have sex with men and transgender women demonstrates the need for eHealth interventions to optimize the HIV care continuum. Issue 7 (3rd July 2017) - Anand, Tarandeep; Nitpolprasert, Chattiya; Kerr, Stephen J.; Muessig, Kathryn E.; Promthong, Sangusa; Chomchey, Nitiya; Hightow-Weidman, Lisa B.; Chaiyahong, Prachya; Phanuphak, Praphan; Ananworanich, Jintanat; Phanuphak, Nittaya
ABSTRACT: In Thailand, young men who have sex with men (YMSM) and transgender women (TG) are disproportionately affected by HIV and have suboptimal care continuum outcomes. Although Thai YMSM and young TG are early adopters of emerging technologies and have high Internet and technology access and utilization, the potential of technology has not been harnessed to optimize the HIV treatment cascade. We interviewed 18 behaviorally HIV-infected YMSM and young TG regarding care challenges, identified how eHealth could address care needs, and elicited preferences for eHealth interventions. Participants reported struggling with individual and societal-level stigma which negatively impacted linkage to and retention in care, and antiretroviral therapy adherence. YMSM and young TG described inadequate in-person support services and heavily relied on random online resources to fill information and support gaps, but sometimes viewed them as untrustworthy or inconsistent. Participants universally endorsed the development of eHealth resources and proposed how they could ameliorate individual-level fears over stigma and improve public perceptions about HIV. Personalized and integrated eHealth interventions with interactive, user-driven structures, credible content, rewards for engagement, real-time counseling and reminder support could help overcome barriers YMSM and young TG face in traditional HIV healthcare systems and have the potential to improve care outcomes.